Awareness of antimicrobial resistance and antibiotic use among poultry farmers in Accra, Ghana: A cross-sectional survey - Henry Kwadwo Hackman; Lawrence Annison; Reuben Essel Arhin; Ebenezer Krampah Aidoo; Evans Andoh Wilberforce; Alice Constance Mensah; Louis Appiah; Sharon Annison; Matilda Ayim-Akonor (PLoS ONE, 2025)
Background Antimicrobial resistance (AMR) in livestock production is an escalating global public health threat, fuelled in part by the misuse of antibiotics in animal farming. This study aimed to assess the knowledge, attitudes, and practices regarding antimicrobial use and AMR among poultry farmers in Accra, Ghana. Methods A cross-sectional survey of 400 poultry farmers in five communities across the Greater Accra Region was conducted using a structured questionnaire. The survey collected data on demographics, AMR awareness, antibiotic usage practices (treatment, prophylaxis, or growth promotion), and commonly used antibiotic classes from 14th March to 26th September 2023. Descriptive statistics summarized the findings. Associations between farmer characteristics (age, gender, education, location) and antimicrobial self-medication (treating poultry without veterinary consultation) were evaluated using chi-square tests. A multivariate logistic regression model identified independent demographic predictors of self-medication, with significance set at p < 0.05. Results Most farmers (70%) reported self-medicating sick poultry without veterinary consultation, and only 35% of respondents were aware of the concept of AMR. Antibiotics were predominantly used for treating illness (63% of farmers), while 20% used them for prophylaxis and only 4% for growth promotion. The most administered antibiotic classes were tetracyclines (26%), nitrofurans (24%), aminoglycosides (18%), penicillins (17%), and fluoroquinolones (10%). Male farmers and those over 30 years had significantly higher rates of antimicrobial self-medication than female and younger farmers (p < 0.001), and in multivariate analysis, being male (odds ratio ~4.9), age > 30 years (OR ~4.6), and farming in a rural area (OR ~2.7) were independent predictors of self-medication with antibiotics. Conclusions Inappropriate antibiotic use is highly prevalent among poultry farmers in Accra, and awareness of AMR is low. These findings underscore an urgent need to strengthen veterinary oversight and enforce regulations on antibiotic sales. Educating farmers through a One Health approach is also recommended to promote prudent antibiotic use and curb the rise of antimicrobial resistance.